Perinatal Outcome in Term Pregnancy with Isolated Oligohydramnios: Retrospective Observational Study - Adhikari, Ayushma; Gurung, Tika Kumari; Adhikari, Shree Prasad (Journal of Nepalgunj Medical College, 2021)
Introduction: Isolated Oligohydramnios complicates 3 to 5% of pregnancy at term both in terms of fetal outcome and mode of delivery. Aims: To study the perinatal outcome in isolated oligohydramnios (Amniotic Fluid Index≤8) and compare the outcome between Borderline (Amniotic Fluid Index=5.1-8 cm) and Severe (<5 cm) oligohydramnios. Methods: Retrospective observational study of pregnancy outcome with isolated oligohydramnios (Amniotic Fluid Index≤8 cm) at term was carried out in Gandaki Medical College Teaching Hospital, Pokhara for one year from January 2019 to December 2019. Patients were divided into Borderline Oligohydramnios (Amniotic Fluid Index=5.1 to 8 cm) and Severe Oligohydramnios (Amniotic Fluid Index ≤5 cm). The two groups were compared in terms of fetal outcome like: meconium passage, low birth weight, low APGAR (Appearance, Pulse, Grimace, Activity and Respiration) score at 1 and 5 min, Neonatal Intensive Care Unit (NICU) admission and neonatal death. Similarly mode of delivery was also compared. Results: There were total of 100 patients with isolated oligohydramnios. Of which 51(51%) were with Borderline Oligohydramnios and 49(49%) with Severe Oligohydramnios. The incidence of adverse perinatal outcome and caesarean delivery was high in patients with isolated oligohydramnios. When compared with the two groups there was significant difference in terms of meconium passage (11% vs 48.9%), low birth weight (5.8% vs 18%), low APGAR (Appearance, Pulse, Grimace, Activity and Respiration) score at 1 min (1.9% vs 14%), NICU (Neonatal Intensive Care Unit) admission (11% vs 67%) and Caesarean delivery (39% vs 79.5%). Conclusion: Isolated oligohydramnios at term has been associated with an increased risk for caesarean delivery for fetal distress and adverse perinatal outcomes. Severe oligohydramnios is a sensitive predictor for the adverse perinatal outcome both in terms of fetal outcome and termination of pregnancy.